Common law constitutional rights - Elliott, Mark, 1975-; Hughes, Kirsty Elizabeth (Oxford ; Hart, 2020)
"This book is the first collection of its kind exploring common law constitutional rights. It offers a detailed and comparative analysis of the content and role of individual common law constitutional rights in judicial decision-making; and a series of essays offering a range of perspectives on the constitutional significance and rights implications of this development. There is a developing body of legal reasoning in the United Kingdom Supreme Court that has championed common law constitutional rights. Indeed various members of the senior judiciary have asserted the primary role of common law constitutional rights and critiqued legal arguments based first and foremost on the Human Rights Act 1998. This shift in legal reasoning has created a sense amongst both scholars and the judiciary that something significant is happening here, and was recently described by Lady Hale as 'UK constitutionalism on the march'. This collection brings together leading constitutional scholars to analyse this significant development for the first time"--
Common Law Constitutional Rights : An Introduction / Mark Elliott and Kirsty Hughes -- The Mythology and the Reality of Common Law Constitutional Rights -- to Bodily Integrity / Natasa Mavronicola -- Access to Justice : From Judicial Empowerment to Public Empowerment / -- Se-shauna Wheatle -- A Constitutional Right to Property? / Tom Allen -- A Common Law Constitutional Right to Privacy : Waiting for Godot? / Kirsty Hughes -- Freedom of Expression and the Right to Vote : A Tale of Two Rights / Jacob Rowbottom -- Searching for a Chimera? : Seeking Common Law Rights of Freedom -- of Assembly and Association / Gavin Phillipson -- Equality : A Core Common Law Principle, or 'Mere' Rationality? / Colm O'Cinneide -- The Fundamentality of Rights at Common Law / Mark Elliott -- Fundamental Common Law Rights and Legislation / Alison L Young -- Common Law Constitutional Rights and Executive Action / Joanna Bell -- Common Law Constitutional Rights at the Devolved Level / Brice Dickson -- The Reach of Common Law Rights / Thomas Fairclough.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Constitutional law -- Great Britain; Common law -- England; Constitutional & administrative law,Human rights & civil liberties law,Human rights; Electronic books